IMPROVING STUDENTSâ READING COMPREHENSION AT ZAKAH AND WAQF MANAGEMENT CLASS USING COLLABORATIVE STRATEGIC READING - Suryaningsih, Ruliq (EDUKASI: Jurnal Pendidikan Islam, 2018)
This research is aimed at finding whether or not Collaborative Strategic Reading (CSR) can improve studentsâ reading comprehension in Zakah and Waqf Management class, and identifying the classroom situation when Collaborative Strategic Reading (CSR) is implemented in the teaching and learning process. The method used in this research was an action research. The research was conducted in two cycles at the second-semester students of Zakah and Waqf Management of IAIN Ponorogo at the academic year of 2017/2018. The research findings show that the use of Collaborative Strategic Reading could improve studentsâ reading comprehension and classroom situation of English class. The improvement of students reading comprehension is shown by students being able to:  find the main idea of the text, find implicit information of the text, find the explicit information from the text, infer the meaning of the certain word (vocabulary), and determine references. Besides, the improvement of studentsâ reading comprehension can be seen from the improvement of the mean score of pre-test, first post-test and second post-test that are 55.30, 66.36 and 75.06. Increasing the classroom situation is indicated by almost all students giving more attention and most students are more active during English class.